Life's Essential 8 and carotid artery plaques: the Swedish cardiopulmonary bioimage study - Herraiz-Adillo, Ángel; Ahlqvist, Viktor H.; Higueras-Fresnillo, Sara; Berglind, Daniel; Wennberg, Patrik; Lenander, Cecilia; Daka, Bledar; Ekstedt, Mattias; Sundström, Johan; Ortega, Francisco B.; Östgren, Carl Johan; Rådholm, Karin; et al. (Frontiers in Cardiovascular Medicine, 2023)
Background To quantify cardiovascular health (CVH), the American Heart Association (AHA) recently launched an updated construct of the “Life's Simple 7” (LS7) score, the “Life's Essential 8” (LE8) score. This study aims to analyse the association between both CVH scores and carotid artery plaques and to compare the predictive capacity of such scores for carotid plaques. Methods Randomly recruited participants aged 50–64 years from the Swedish CArdioPulmonary bioImage Study (SCAPIS) were analysed. According to the AHA definitions, two CVH scores were calculated: i) the LE8 score (0, worst CVH; 100, best CVH) and two different versions of the LS7 score [(0–7) and (0–14), 0 indicating the worst CVH]. Ultrasound-diagnosed carotid plaques were classified as no plaque, unilateral, and bilateral plaques. Associations were studied by adjusted multinomial logistic regression models and adjusted (marginal) prevalences, while comparison between LE8 and LS7 scores was performed through receiver operating characteristic (ROC) curves. Results After exclusions, 28,870 participants remained for analysis (50.3% women). The odds for bilateral carotid plaques were almost five times higher in the lowest LE8 (<50 points) group [OR: 4.93, (95% CI: 4.19–5.79); adjusted prevalence 40.5%, (95% CI: 37.9–43.2)] compared to the highest LE8 (≥80 points) group [adjusted prevalence 17.2%, (95% CI: 16.2–18.1)]. Also, the odds for unilateral carotid plaques were more than two times higher in the lowest LE8 group [OR: 2.14, (95% CI: 1.82–2.51); adjusted prevalence 31.5%, (95% CI: 28.9–34.2)] compared to the highest LE8 group [adjusted prevalence 29.4%, (95% CI: 28.3–30.5)]. The areas under ROC curves were similar between LE8 and LS7 (0–14) scores: for bilateral carotid plaques, 0.622 (95% CI: 0.614–0.630) vs. 0.621 (95% CI: 0.613–0.628), P = 0.578, respectively; and for any carotid plaque, 0.602 (95% CI: 0.596–0.609) vs. 0.600 (95% CI: 0.593–0.607), P = 0.194, respectively. Conclusion The new LE8 score showed inverse and dose-response associations with carotid plaques, particularly bilateral plaques. The LE8 did not outperform the conventional LS7 score, which showed similar ability to predict carotid plaques, especially when scored as 0–14 points. We conclude that both the LE8 and LS7 may be useful in clinical practice for monitoring CVH status in the adult population.